Kualitas Bakteriologis Alat Makan, Personal Hygiene, Dan Keadaan Sarana Sanitasi Warung Kopi - Rochmawati, Amanda Evi; Rachmaniyah; Rusmiati (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2021)
Inadequate sanitary conditions and poor hygiene practices of coffee shop employees can be one of the causes of germs on the tableware used. Contamination can occur in food that is in direct contact with unclean cutlery and contains microorganisms, this can lead to disease in the digestive system. The purpose of this study was to identify the bacteriological quality of cutlery, personal hygiene, and state of sanitation facilities. This type of research is descriptive. The population of this study were 15 coffee shops with a total sample of 10 samples of cutlery and 5 samples of clean water which were taken by purposive sampling. Analysis of data regarding the bacteriological quality of cutlery, personal hygiene, and sanitation conditions were based on laboratory results and observation sheets. The results of the research on glass utensils and coasters, parameter E.coli 100% met the requirements, while the total plate count parameter for cutlery and MPN Coliform clean water at five coffee shops in Kendangsari showed 100% did not meet the requirements, the application of the cutlery washing technique was of sufficient value ( 64%), the sanitation condition of the coffee shop is of sufficient value (61%), and the personal hygiene of the employees is of sufficient value (58%). It is hoped that the relevant agencies are willing to provide counseling on techniques for washing cutlery, as well as the application of personal hygiene to coffee shop employees in Kendangsari so that the quality of cutlery is maintained.